SDN Controller Placement With Availability Upgrade Under Delay and Geodiversity Constraints - Santos, Dorabella (2021)
An inherent problem in Software-Defined Networking (SDN) is the Controller Placement Problem, which addresses how many controllers to deploy in the network, and where to place them. Several variants of this problem have been addressed and researched to find the placements that adapt best to different contexts. In this paper, we address a more complex variant of this problem, to satisfy QoS requirements and to offer robustness against disaster-based failures. We address the joint optimization problem of controller placement and finding a tree subgraph which can be upgraded to have enhanced availability, in order to satisfy delay and availability constraints. Additionally, we consider geodiversity constraints as a way to enhance robustness to disaster-based failures.